ETHNOPHARMACOLOGICAL REVIEW OF NATURAL PRODUCTS IN CANCER PREVENTION AND THERAPY - Ayoub, Zeenat; Mehta, Archana; Mishra, Siddhartha Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
The World Health Organization reports that approximately 80% population from developing countries are facing complications from synthetic drugs used in maintaining their primary health-care needs. The chemotherapeutic strategies are very striking and have earned serious concern as potential means of controlling the incidence of this dreadful disease. However, the major problem in cancer is the long lasting toxicity of the well reputable chemical drugs. Since ancient times, medicinal plants have attracted enormous attention, to fight against various diseases with their broad-spectrum biological and therapeutic properties. Although plants, phytochemicals and their analogues have been confirmed to be safe and effective, having strong anticancer properties. A number of pharmaceutical agents with diverse chemical structures of natural origin from plants have been discovered as anticancer agents such as vincristine, vinblastine, podophyllotoxin, camptothecin, taxol, resveratrol, withaferin A, quercetin, and curcumin. Further modifications of these phytochemicals led to the development of numerous outstanding molecules such as drugs like topotecan, irinotecan, taxotere, etoposide, and teniposide. In this in-depth review, we meticulously investigated the selected medicinal plants for their anticancer properties. In particular, novel compounds from plants have beneficial effects on human health. Our observations suggest the preventive and therapeutic use of phytochemicals in managing various human malignancies.